Proposed conceptual design model of persuasive game for upper limb for stroke rehabilitation - Omar, M.Y.B. (Institute of Electrical and Electronics Engineers Inc., 2019)
The gamification of stroke rehabilitation may increase patient's motivation and engagement towards their rehabilitation activity and hence contributes to faster recovery. Apart from the interactive experience that games offer, it also may be used as a persuasive tool. In this view, games may be used to persuade stroke patients in shaping a good behavior towards their rehabilitation activity. This paper reports our proposed conceptual design model of building persuasive game for stroke patients that follows the Persuasive System Design Model. We incorporate the persuasive software features that includes reduction, tailoring, self-monitoring, and rewards. The proposed game architecture is also discussed in this paper. Â© 2019 IEEE.